Numerical investigation of droplet spreading and heat transfer on hot substrates. (June 2018) - Cheng, Yongpan; Wang, Fan; Xu, Jinliang; Liu, Dong; Sui, Yi
Graphical abstract: Highlights: Droplet spreading is simulated with axisymmetric model with level set method. Dynamics of moving contact line can be described well by molecular kinetic theory. Maximum heat transfer occurs at the end of capillary-inertial spreading stage. Cold substrate can promote spreading and hot substrate can retard spreading. Abstract: Droplet spray cooling has wide applications in electronic cooling, steam generators, evaporators and condensers etc due to its high efficiency. The cooling effect depends on the droplet spreading dynamics greatly. In our study the transient two-dimensional axisymmetric model for droplet cooling is developed with a level set method, where the dynamics of the moving contact line is described with the Molecular Kinetic Theory (MKT). After validation with experimental data, the effect of impact velocity, surface tension, initial droplet radius, equilibrium contact angle and liquid viscosity on droplet spreading is investigated. It is found that the dynamics of the moving contact line can be described accurately with MKT, and the predicted droplet spreading radius agrees quite well with the experimental data, while the Constant Contact Angle (CCA) model overpredicts the droplet spreading rate. The maximum heat flux occurs at the point when the droplet spreading transits from capillary-inertial spreading to capillary-viscous spreading. The droplet spreading rate will increase with the increasing impact velocity, surface tension and initial radius, or decreasing equilibrium contact angle and liquid viscosity. Due to the effect of thermo-capillary force, the cold substrate can promote the droplet spreading, and the hot substrate can retard the droplet spreading. These findings may be of great significance for effective droplet spreading cooling.